Correlation Analysis of Chaige Qinlian Decoction and Acupuncture Combined Intervention on Prognosis of Children with Pneumonia. (15th December 2021) - Sun, Qi; Yu, Hanshu; Shang, Yun; Cao, Yan
Abstract : Background . Traditional Chinese medicine (TCM) treatment is of great importance to improve the clinical symptoms of children with pneumonia, and this study was conducted in this context. Methods . The clinical data of 82 child patients with pneumonia admitted to our hospital from February 2019 to February 2020 were retrospectively analyzed, and the patients were divided into the conventional group and the combined group according to the parity of their admission numbers, with 41 cases each. Conventional Western medicine therapy was given to children in the conventional group, and on this basis, acupuncture combined with Chaige Qinlian decoction was performed on children in the combined group, so as to evaluate the clinical application value of combined treatment and analyze its relationship with prognosis by recording the recovery time of each symptom, serum indicators, and immune indicators. Results . Children in the combined group had significantly shorter recovery time of each symptom and lower mean CPIS scores after treatment than the conventional group (P < 0.001 ); the TCM symptom scores at T1 (1 d after treatment), T2 (3 d after treatment), T3 (7 d after treatment), and T4 (10 d after treatment) of children in the combined group were significantly higher than those in the conventional group (P < 0.05 ); various immune indicators of the combined group before and after treatment were significantly different (P < 0.001 ), and after treatment, the combined group obtained significantly higher IgG levels and lower IgA, complement C3, and complement C4 levels than the conventional group (P < 0.001 ); and there was a positive correlation between the CPIS scores and serum IL-8, IL-6, and CRP levels at the first day ( r  = 0.706, 0.712, 0.734, P < 0.001 ). Conclusion . Acupuncture combined with Chaige Qinlian decoction can effectively shorten the course of disease, reduce the levels of serum inflammatory factors, and improve the immune function of body for child patients with pneumonia. Serum IL-8, IL-6, and CRP levels in child patients can reflect the clinical prognosis, with higher levels indicating worse prognosis.